Implementation of OSH in SMEs in Seri Iskandar Perak / Berenice Charissa Philip, Cassandra Anne Leonard Libau and Hafizah Juhari - Philip, Berenice Charissa; Leonard Libau, Cassandra Anne; Juhari, Hafizah (2010)
The implementation of OSH in the SME companies has been under intensive research over the last few decades but the application of these standard legislative guidelines as practical solution is still at its early stage. Overall, there were some issues that relevant to the studies and needed much attention. Based on the findings from the articles and the accidents rates happened, there were some conditions that concern the researchers and the reason for this topic as the Research project title. The objectives of this project are to identify the knowledge level among employees regarding the understanding and awareness of OSH in workplace and also to identify how successful is the implementation of OSH in workplace based on OSH act. Based on the findings, there were various answers from different demographic values, in term of their knowledge and also awareness level. Most of the respondents were aware about OSH and have received OSH benefits before. However, some of them were unaware of this matter and also stated that there were lack of training and also safety precaution in their workplace. The research conducted concluded that company size and financial situation affect the implementation of OSH in workplace. In order to achieve OSH implementation successfully in workplace, it was recommended that top management should take action and shows more support on overcoming this matter more seriously. By implementing OSH more effectively according to the legal standard and certified policies, the reputation and also the company images can be well-preserved.